Physiopathological Implications of 7TM Receptors - Cygankiewicz, Adam I. (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
Seven-transmembrane (7TM) receptors are one of the most important proteins involved in perception of extracellular stimuli and regulation of variety of intracellular signaling pathways. Divergence of receptor types, their ligands and signaling pathways makes 7TM receptors important factors in pathology of many diseases. This review focused on the main diseases in which involvement of 7TM receptors was established e.g., retinitis pigmentosa, severe obesity, and dwarfism. Recent findings of aberrant expression of 7TM receptors in development of cancer were also summarized.